Analgesic Management of Pain in Elite Athletes: A Systematic Review. Issue 5 (September 2018) - Harle, Christopher A.; Danielson, Elizabeth C.; Derman, Wayne; Stuart, Mark; Dvorak, Jiri; Smith, Lisa; Hainline, Brian
Abstract : Objective: To identify the prevalence, frequency of use, and effects of analgesic pain management strategies used in elite athletes. Design: Systematic literature review. Data Sources: Six databases: Ovid/Medline, SPORTDiscus, CINAHL, Embase, Cochrane Library, and Scopus. Eligibility Criteria for Selecting Studies: Empirical studies involving elite athletes and focused on the use or effects of medications used for pain or painful injury. Studies involving recreational sportspeople or those that undertake general exercise were excluded. Main Results: Of 70 articles found, the majority examined the frequency with which elite athletes use pain medications, including nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids, anesthetics, and opioids. A smaller set of studies assessed the effect of medications on outcomes such as pain, function, and adverse effects. Oral NSAIDs are reported to be the most common medication, being used in some international sporting events by over 50% of athletes. Studies examining the effects of pain medications on elite athletes typically involved small samples and lacked control groups against which treated athletes were compared. Conclusions: Existing empirical research does not provide a sufficient body of evidence to guide athletes and healthcare professionals in making analgesic medication treatment decisions. Based on the relatively robust evidence regarding the widespread use of NSAIDs, clinicians and policymakers should carefully assess their current recommendations for NSAID use and adhere to a more unified consensus-based strategy for multidisciplinary pain management in elite athletes. In the future, we hope to see more rigorous, prospective studies of various pain management strategies in elite athletes, thus enabling a shift from consensus-based recommendations to evidence-based recommendations. Abstract : Supplemental Digital Content is Available in the Text.